2018
DOI: 10.4236/ojacct.2018.71007
|View full text |Cite
|
Sign up to set email alerts
|

Managerial Overconfidence and the Value Adjustment Mechanism

Abstract: Using the M & A event of A-share listed companies from 2008 to 2013, which contains the value adjustment mechanism, as a sample, the paper is intended to explore the influence of managerial overconfidence on the performance growth rate and the relationship between the promise of profit growth rate and the performance of M & A. The results show that overconfident managers tend to accept higher performance growth rate, and this tendency is more obvious in private enterprises. The further study found that the hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…After the M&A, under the influence of incentive effect and synergy effect, the target party will rely on resource reallocation, technological innovation, and human capital under the advanced management concept brought by the M&A, and exert subjective initiative to improve the financial situation of the enterprise and complete the promised performance to enhance the M&A performance [2,27]. Further research in this paper agrees with this view, as shown in Table 4, that performance commitments promote improved M&A performance, but this effect is only significant in the short term, and in the long term there is a queue for performance commitments [22], with M&A performance showing an inverted U-shaped curve that rises and then falls as performance commitments increase. This is because excessive performance commitments far exceed the profitability of the target party and may be met in the short term by manipulating profits, but are unable to sustain high performance returns in the long term [34], resulting in a significant decline in M&A performance.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…After the M&A, under the influence of incentive effect and synergy effect, the target party will rely on resource reallocation, technological innovation, and human capital under the advanced management concept brought by the M&A, and exert subjective initiative to improve the financial situation of the enterprise and complete the promised performance to enhance the M&A performance [2,27]. Further research in this paper agrees with this view, as shown in Table 4, that performance commitments promote improved M&A performance, but this effect is only significant in the short term, and in the long term there is a queue for performance commitments [22], with M&A performance showing an inverted U-shaped curve that rises and then falls as performance commitments increase. This is because excessive performance commitments far exceed the profitability of the target party and may be met in the short term by manipulating profits, but are unable to sustain high performance returns in the long term [34], resulting in a significant decline in M&A performance.…”
Section: Discussionsupporting
confidence: 62%
“…Some scholars believe that the performance compensation commitment system has the function of signal transmission and incentive [18][19][20][21]. In the case of information asymmetry, this mechanism aims to alleviate the problems related to valuation uncertainty and protect the interests of investors while delivering good news to the outside world, in order to achieve mutual benefit and win-win results [22,23]. Meanwhile, the acquired party will make more efforts to avoid penalties and obtain rewards after signing the performance compensation commitment [24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%